THEORETICAL ASPECTS OF INTERACTION OF THE FINANCIAL AND REAL ECONOMIC SECTORS - Руденко , Микола (Socio-economic relations in the digital society, 2019)
Тhe theoretical aspects of the interaction of the financial and real sectors of the economy are researched. The analysis of economic flows and theories of convergence and divergence of the above sectors is carried out. It was found that the preconditions for interaction between the real and financial sectors within individual countries and regions are too heterogeneous. It is determined that the modern financial sector is an over-complicated system in which participants have the opportunity to single rotation of financial assets independently of the rotation of real goods. A clear distinction is made between the prices of goods in the cash market and the prices of financial instruments that are essentially derived from commodity markets. Emphasizing the stability of the relationship between the real and the financial sector, it has been proved that the nature of the mutual influence has changed significantly with the development of society, science, technologies, and communications.